Student's Capability In Drawing Conclusion From Argumentative Text At The Eleventh Grade Of SMA N I Kradenan In 2013/2014 Academic Year - Kurniawati, Estri; , Drs. Djoko Srijono, M.Hum; , Dr. Anam Sutopo, M.Hum (2014)
The aims of this research are at describing: 1) student's capability in drawing conclusion from argumentative text, and 2) the strategies that uses by the eleventh grade students in drawing conclusion from argumentative text. This research is descriptive research as an approach to collect and analyze the data. The object of this research is student's capability in drawing conclusion from argumentative text at eleventh grade of SMA N I Kradenan in 2013/2014 academic year. The methods of collecting data are interview, test, and analyzing document. The researcher analyzed the student's capability in drawing conclusion based on 4 concepts, they are: (1) complete conclusion that consists of 4 concepts, (2) incomplete conclusion that consists of 4 concepts, (3) incomplete conclusion that consist of 2 concepts, and (4) incomplete conclusion that consists of 1 concept. Based on the analyzed data, it can be concluded that the student's capability in drawing conclusion from argumentative text at the eleventh grade of SMA N I Kradenan is good. More than 50% students or 25 students from 38 students are capable of drawing conclusion perfectly without seeing the use of their grammar and structure. There are two strategies used by students, they are: 1) translating the text into Indonesian, and 2) reading the text then asking their teacher when they have difficulties about the text.